MÚSICA Y MERCENARIOS EN LA FUNDACIÓN DE CIUDADES ARGENTINAS: BIRIMBAOS DEL SIGLO XVII EN BUENOS AIRES Y CATAMARCA - Ana Igareta; Daniel Schávelzon (Revista de Arqueología Histórica Argentina y Latinoamericana, 2009)
Musical instruments travelled around the world with humankind since it became a new specie. The arrival of European conquerors to America during the XVth century brought to the continent a large set of new instruments which were quickly incorporated to the material culture of the rising colonial society. Historical records indicated that Jew’s harp or guimbarda was one of the most widely spread, although their meagre size and ferrous composition difficulty their long term conservation and made them virtually invisible to the archaeological investigation. The finding of two units in perfectly identifiable contexts in the República Argentina –one in Buenos Aires city and another one in the west of Catamarca province– constitutes some exceptional cases in such sense, allowing further exploration. This work presents a brief compilation of the information available on jew’s harps and its journey to America, at well as details the particular characteristics of the units mentioned before and their relevance in the contexts in which they were found